OTU-002 HLA-DQA1 contributes to the development of antibodies to anti-TNF therapy in crohn's disease. (8th June 2018) - Sazonovs, Aleksejs; Kennedy, Nicholas A; Bewshea, Claire; Moutsianas, Loukas; Walker, Gareth J; Lange, Katrina De; Goodhand, James R; Anderson, Carl; Barrett, Jeff; ,; Ahmad, Tariq
Abstract : Background: Immunogenicity to anti-TNF therapy is a major cause of loss of response, treatment discontinuation and hypersensitivity reactions and currently cannot be predicted prior to treatment. A number of factors have been associated with the risk of immunogenicity, but knowledge of the cellular and molecular mechanisms remain limited. Our aim was to investigate genetic susceptibility to immunogenicity. Methods: The PANTS (Personalised Anti-TNF Therapy in Crohn's disease) study is a 3 year prospective observational UK-wide study investigating primary non-response, loss of response and adverse drug reactions to the anti-TNF drugs infliximab and adalimumab. Anti-drug antibodies (ADAs) were measured serially at trough using the IDKmonitor total ADAb ELISA assay. Immunogenicity was defined as (a) ADA titre ≥10 AU/ml and (b) ADA titre ≥10 AU/ml with no detectable drug. A genome-wide association study (GWAS) was carried out on imputed genotype data using a Cox proportional hazards model incorporating the anti-TNF used and presence of concomitant immunomodulator as covariates (SurvivalGWAS_SV v1.3.1). Results: After quality control, we had genotype data for 1284 patients followed prospectively for a minimum of 12 months since starting anti-TNF therapy. Using a Cox proportional hazards model and an immunogenicity definition of ADAs titre ≥10 AU/ml we identified a genome-wide association on chromosome 6 (top SNP rs74291249 with p=5.6 × 10 −13 ). We imputed the HLA alleles at 2- and 4-digit resolution using the HIBAG package and demonstrated that this signal was driven by HLA-DQA1*05 for both infliximab and adalimumab. No additive effect of having two DQA1*05 was seen. Figures 1 and 2 show immunogenicity-free survival stratified by HLA-DQA1*05 genotype and concomitant immunomodulators at baseline. Conclusion: We have demonstrated that immunogenicity to anti-TNF is determined by HLA variants. Pre-treatment genetic testing might allow the use of individual risk profiles and targeted use of immunomodulatory therapies to deliver more durable, safe and cost-effective anti-TNF therapy.